PERANCANGAN SISTEM INFORMASI PERPUSTAKAAN BERBASIS WEB PADA SMK NEGERI 1 PULOAMPEL SERANG-BANTEN - Ahmad Sofan Ansor; Rosdiana Rosdiana; Hendrawan Hendrawan (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2022)
The library is one of the schools supporting facilities that play an important role in providing reading material and additional student material that can support student learning success. The library SMK Negeri 1 Puloampel Serang-Banten still uses a manual system for reporting the registration process, member data collection, book data collection, borrowing and returning transaction data collection. This is very ineffective and ineffective given that manual system hamper librarian data processing and report generation performance, with the potential risk of data loss or corruption. With these problems, what is needed is a computerized system that can manage data accurately, effectively and efficiently. This study aims to improve the efficiency of library work and help solve problems that arise in the library of SMK Negeri 1 Puloampel. The method used in software development using the waterfall model means the system works sequentially or linearly. Data collection methods are observation, interviews and literature study, using the PHP programming language and supported by a MySQL database. The library information system is expected to improve the performance of library managers in navigating the registration process, borrowing and returning library books, and writing reports. Keywords: Design, Library, Website, Waterfall